Effect of persistent moderate viremia on disease progression during HIV therapy. - Raffanti, Stephen P; Fusco, Jennifer S; Sherrill, Beth H; Hansen, Nellie I; Justice, Amy C; D'Aquila, Richard; Mangialardi, Wendy J; Fusco, Gregory P (Journal of acquired immune deficiency syndromes (1999), 2004)
Although highly active antiretroviral therapy has been shown to lower plasma HIV-1 RNA in HIV infection, many patients do not reach the target goal of undetectable viremia. We evaluated whether risk of clinical progression varies by level of viral suppression achieved.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Cohort Studies; Disease Progression; Drug Therapy, Combination; Female; HIV Infections; HIV-1; Humans; Male; Proportional Hazards Models; Reverse Transcriptase Inhibitors; RNA, Viral; United States; Viral Load; Viremia